PENGEMBANGAN ALAT PERAGA MATEMATIKA BERBASIS AUDIO PADA POKOK BAHASAN KELILING DAN LUAS SEGITIGA UNTUK SISWA TUNANETRA SMPLB TPA JEMBER - Tirta, T; Susanto, S; Kristiani, Arika Indah (KadikmA, 2013)
Abstract.The aimof this research is to develop an audio based math media.It will help blind stunentd to understand thecircumferenceandtriangle area concepts. The methodis obtained from modifyng Four D modeland data collecting proccessin this research usequestionnaires andobservation. The validation results done by computerexpert, education expert and math teacherof SMPLBclass VII-A shows that 87.91% of the criteria have been fullfiled the validityand no revision required. The next stepis implementation test forblind studentsof class VII. The media test results shows that 92.85% have been fulfilledthevalidity. It means that the media has a very valid category and no revision required. The development result ofaudio based math media is an executable software. The product of this research are 6 units audio based math media and the manual book. Key Words:development research, audio, blind students